Creating accessibility in academic negotiations. Issue 3 (March 2023) - Kong, Jennifer H.; Vasquez, Claudia G.; Agrawal, Sweta; Malaney, Prerna; Mikedis, Maria M.; Moffitt, Andrea B.; von Diezmann, Lexy; Termini, Christina M.
Abstract: The process of evaluating and negotiating a tenure-track job offer is unstructured and highly variable, making it susceptible to bias and inequitable outcomes. We outline common aspects of and recommendations for negotiating an academic job offer in the life sciences to support equitable recruitment of diverse faculty.